Nut Consumption and Risk of Stroke in US Male Physicians - Djoussé, Luc (2010)
BACKGROUND AND AIMS: While nut consumption has been shown to lower the risk of hypertension and coronary disease, it is not known whether nut consumption is associated with the risk of stroke. We sought to examine whether nut consumption is associated with total and subtypes of stroke. METHODS: Prospective cohort of 21,078 participants from the Physicians’ Health Study (1982–2008) who were free of stroke at baseline. Nut consumption was assessed using a simple 19-item food questionnaire and stroke cases were confirmed after reviewing medical records. We used Cox proportional hazards regression to estimate relative risks of total, ischemic, and hemorrhagic stroke according to consumption of any nuts. RESULTS: During a mean follow up of 21.1 years, 1,424 incident cases of stroke occurred (219 hemorrhagic, 1,189 ischemic, and 16 of undetermined cause). There was no statistically significant association between nut consumption and total or ischemic stroke. In contrast, there was a suggestive non-linear relation between nut intake and hemorrhagic stroke: compared to subjects who did not consume nuts, multivariable adjusted hazard ratios (95% CI) for hemorrhagic stroke for subjects consuming nuts < 1, 1, 2–4, 5–6, and ≥ 7 times/week were 1.13 (0.78–1.62), 1.05 (0.70–1.58), 0.49 (0.27–0.89), 1.50 (0.79–2.84), and 1.84 (0.95–3.57), respectively (p for quadratic trend 0.12). CONCLUSIONS: Our data showed no association between nuts and ischemic stroke and suggested a J-shaped relation between nut consumption and hemorrhagic stroke. Replication of our findings in the general population is warranted.